Respuesta :
Answer:
=−3y+8z
Step-by-step explanation:
2x−2y+5z−2x−y+3z
=2x+−2y+5z+−2x+−y+3z
=2x+−2y+5z+−2x+−y+3z
=(2x+−2x)+(−2y+−y)+(5z+3z)
=−3y+8z
The simplification of the given expression 2x − 2y + 5z − 2x − y + 3z will be −3y+8z.
What is an expression?
A mixture of variables, numbers, addition, subtraction, multiplication, and division are called expressions.
An expression is a mathematical proof of the equality of two mathematical expressions.
A statement expressing the equality of two mathematical expressions is known as an equation.
Given,
2x − 2y + 5z − 2x − y + 3z
Combining likely terms
⇒ 2x+−2y+5z+−2x+−y+3z
⇒(2x+−2x)+(−2y+−y)+(5z+3z)
⇒ −3y+8z
Hence"The simplification of the given expression 2x − 2y + 5z − 2x − y + 3z will be −3y+8z".
To learn more about expression
https://brainly.com/question/14083225
#SPJ5